Intermittent fasting positively modulates human gut microbial diversity and ameliorates blood lipid profile - Khan, Muhammad Nadeem; Khan, Sidra Irshad; Rana, Madeeha Ilyas; Ayyaz, Arshad; Khan, Muhammad Yousaf; Imran, Muhammad (Frontiers in Microbiology, 2022)
Aim The aim was to evaluate the impact of intermittent fating (IF) on the diversity of gut microbiota and its impact on blood lipid profile and human physiology. Methods and Results: Fourteen healthy females and thirty-one males included in the study: their blood and fecal samples were collected before and at the end of the study. Blood parameters, anthropometric values and gut microbiology were noted to investigate the impact of intermittent fasting (IF) on human gut microbiota and physiology. Our data revealed that IF reduces the body weight and improves blood lipid profile, such as increases high density lipoprotein (HDL) and decreases total cholesterol, triglycerides, low and very low-density lipoprotein levels. IF also decreases culturable aerobic bacterial count and increased fungal count. It was also found that the gut metagenome is altered considerably after IF. The human fecal bacterial diversity exhibited significant changes as in decreased overall bacterial population, increased bacterial diversity (alpha diversity), promoted evenness within bacterial population at species level. Anti-inflammatory bacteria Lactobacillus and Bifidobacterium were favorably increased while Conclusions Collectively, these results indicated that IF could improve lipid profile and body weight in humans, and the potential mechanisms might be via regulating gut microbiota.